Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

No margins: Writing Canadian fiction in lesbian - Lake, Catherine; Holtz, Nairne (Insomniac Press, 2006)
Elegant tomboys, academic femmes, small town kisses, and international dykes; road trip encounters and scenes from a straight bar; questions arising from an in-between culture; the music of travel and hotel room orgasms. Crossing race, culture, and gender constraints, No Margins leads the reader through the lushness of lesbian life and the vastness of Canadian experience.No Margins is a stellar short fiction collection featuring fifteen of Canada's finest contemporary writers, all of whom include lesbian identity as a piece of their selves and their work. These highly acclaimed authors were selected to convey the places we currently inhabit and the future we are forging. The contributors have included notes to accompany their work, thus sharing the creative process and speaking on the politics of lesbian writing. No Margins is an unprecedented anthology, reflecting an esteemed gathering of women who are currently shaping Canadian literature.Featuring the work of: Luanne Armstrong • Dionne Brand • Nicole Brossard • Emma Donoghue • Marion Douglas • Anne Fleming • Jane Eaton Hamilton • Lydia Kwa • Larissa Lai • Ann-Marie MacDonald • Daphne Marlatt • Shani Mootoo • Elizabeth Ruth • Karen X. Tulchinsky • Marnie Woodrow
https://www.deslibris.ca/ID/440108
Keywords: amériques; anthologie; canada; fiction; littérature; outils; ouvrages de références; personnes lesbiennes; ressource en ligne; régions géographiques

Queer migrations: Sexuality, U.S. citizenship, and border crossings - Luibhéid, Eithne; Cantú, Lionel (University of Minnesota Press, 2005)
À l’intersection de la citoyenneté, de la sexualité et de la race, une nouvelle perspective sur l’expérience immigrante Queer Migrations rassemble des chercheurs pour fournir des analyses des normes, des institutions et des discours qui affectent les immigrant.e.s queer de couleur, et propose également des études ethnographiques sur la façon dont ces nouvelleaux arrivant.e.s ont transformé les communautés d'immigrant.e.s établies à Miami, San Francisco et New York. Contributeurices : Martin F. Manalansan IV, Susana Peña, Erica Rand, Timothy Randazzo, Horacio N. Roque Ramírez, Alisa Solomon, Siobhan B. Somerville, Alexandra Minna Stern.
Keywords: amériques; approches et analyses; identités LGBTQIA2+; outils; ouvrages de références; queer; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; états-unis

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Encyclopedia of lesbian, gay, bisexual, and transgender history in America - Stein, Marc (Charles Scribner's Sons/Thomson/Gale, 2004)
A three-volume survey of more than 400 years of lesbian and gay history and culture in the United States, presented through over 500 alphabetically arranged entries. Coverage includes people, public policy, economics, social issues, identities, and culture, among many others. For students, researchers, and general readers.
Keywords: amériques; encyclopédie; identités LGBTQIA2+; outils; ouvrages de références; ressource en ligne; régions géographiques; états-unis